2012
DOI: 10.1177/193229681200600429
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Infusion Set: The Achilles Heel of Continuous Subcutaneous Insulin Infusion

Abstract: Continuous subcutaneous insulin infusion from an insulin pump depends on reliable transfer of the pumped insulin to the subcutaneous insulin depot by means of an insulin infusion set (IIS). Despite their widespread use, the published knowledge about IISs and related issues regarding the impact of placement and wear time on insulin absorption/insulin action is relatively small. We also have to acknowledge that our knowledge is limited with regard to how often patients encounter issues with IISs. Reading pump we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 64 publications
1
144
0
2
Order By: Relevance
“…1 The first involved an 11-year-old female who developed toxic shock syndrome from a Staphylococcus aureus infection after leaving her infusion set in for up to 10 days. 21 Another was a case of death due to bacterial endocarditis that started at the site of infusion set insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The first involved an 11-year-old female who developed toxic shock syndrome from a Staphylococcus aureus infection after leaving her infusion set in for up to 10 days. 21 Another was a case of death due to bacterial endocarditis that started at the site of infusion set insertion.…”
Section: Discussionmentioning
confidence: 99%
“…1 One problem for closed-loop insulin delivery is the limited life span of continuous subcutaneous insulin infusion sets, and the current recommendation is to change the infusion site every 3 days. 1 Evidence about factors that affect infusion set survival is needed to extend infusion site life span.…”
mentioning
confidence: 99%
“…Infection was the most common issue reported in older studies [8,31,32]. Earliest reported data showed that 29 % of patients experienced an infected infusion site at some point, most commonly presenting as cellulitis [8].…”
Section: Infectionmentioning
confidence: 95%
“…However, IIS issues have led to the greatest number of recalls by the FDA in the USA (see above). The pump and the IIS should be considered as parts of a system, rather than as individual components [21]. However, this is not currently the case, as some IISs are cleared as part of the pump system under different product codes and some are cleared as a separate device product code.…”
Section: Insulin Infusion Setsmentioning
confidence: 99%